Assessment the relation between lifestyle with mental health and educational achievement in nursing students - Heidari, Mohammad; Borujeni, Marzieh Borjian; Borujeni, Mansureh Ghodusi; Borujeni, Mansureh Ghodusi; Rezaei, Parvin (Bangladesh Journal of Medical Science, 2019)
Objective: This study was aimed to assess the correlation between lifestyle with mental health and educational achievement ofnursing students. Materials and Methods: This is a descriptivecorrelational study that all students in nursing college in 2015 were selected by the census sampling method. Data gathering tool were standard Walker’s lifestyle questionnaire and General Health Questionnaire-28 and data were analyzed by SPSS/21. Results: The results reported that most subjects (61.01%) displayed moderate levels of lifestyle. In considering domains mental health37.28%, were depression and 34.74% anxiety. Based on the Pearson correlation coefficient test, there was a diverse correlation between lifestyle (p=0.004, r=-0.34) and educational achievement (p=0.001, r=-0.24) with mental health but there was a direct linear correlation between lifestyle and educational achievement. Conclusion: Regarding the role of lifestyle and mental health and to ensure the efficiency and dynamism of the people in the education and prevention of academic failure recommended that be scheduled byimprove methods of lifestyle to promote educational status and activate counseling centers andguidance on psychological issues the mental health. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.722-728